Indonesian EFL students’ perceptions of effective non-native English teachers - Ummi Zurrahmi; Anita Triastuti (Studies in English Language and Education, 2022)
Effective non-native English teachers (NNETs) are essential to facilitate students to develop their English mastery. However, while students are directly affected by teachers’ instructions, they have been limitedly involved in teacher education and development research. The current study aims to explore the qualities of effective non-native English teachers (NNETs) from students’ perspectives in Tanjungpinang, Indonesia. This study was mixed-method research specifically an explanatory sequential design. In the quantitative phase, 380 students were selected using cluster sampling techniques. Meanwhile, in the qualitative phase, six students were purposely selected based on their English proficiency levels and gender. The instruments used were a questionnaire adapted from Park and Lee (2006) and an interview guide. To analyze the questionnaire data, descriptive and inferential statistical analyses were employed. MANOVA test was run to seek significant differences by students’ gender and English proficiency levels. Meanwhile, the qualitative data were coded to identify the emerging patterns. The results show that the qualities concerning teachers’ socio-affective skills gained the highest mean scores compared to those concerning teachers’ subject matter knowledge and pedagogical skills. This study also confirms that there was a significant difference among students in perceiving effective NNETs by English proficiency levels. This study is expected to help various stakeholders to improve pre and in-service EFL teacher education and development in Indonesia.